Primetime Paganism: Popular-Culture Representations of Europhilic Polytheism in Game of Thrones and Vikings - Robert A. Saunders (Correspondences, 2014)
This article provides a critical examination of the politico-religious content of the highly successful television series Game of Thrones and Vikings. By comparing and contrasting two very different representations of ethnically-marked “European” polytheism, I seek to uncover underlying trends in contemporary attitudes towards reconstructed “native faith” among peoples of European origin, particularly in contrast to “imported” monotheisms (Judaism, Christianity, and Islam). This article makes several tentative claims about the protean nature of religious identity in the context of popular culture. First, that traditional lmic treatments of pagans qua villains is shifting, with contemporary popular culture allowing for more nuanced framing of Western forms of polytheism. Secondly, that such popular-culture representations of paganism have direct impact on certain contemporary Pagans’ personal spiritual paths by promoting and influencing the “invention of tradition” among a population which manifests non-traditional religious identities.